Lust, tranquillity and sensuality in French spa towns in the heyday of balneotherapy (the belle époque and the roaring twenties) - Marie-Eve Férérol (Via@)
French spa resorts had their heyday from 1875 to 1915. During this era, the aristocracy and the bourgeoisie would flock to the spa towns. On the pretext of maintaining their health, this clientele was in fact mainly in search of hedonism, idleness and frivolity. There were two reasons for this. One was the expansion in bourgeois morality, and the other was the uncertain future at the turn of the 20th century (the advancing tide of modernity, presages of the 1st World War, etc.). Spa towns thus became ‘safety valves’ (Authier, 1997), another world, an escape from everyday life, where all sorts of transgressions were possible. In this article, we ask how these resorts became ‘destinations of desire’ and what was their level of eroticisation. The eroticisation of spa towns was due as much to their décor as to the uses made of them.